The life and works of Andrzej Panufnik (1914 - 1991) - Bolesławska-Lewandowska, Beata 1974- (Ashgate, 2015)
Sir Andrzej Panufnik was born in Warsaw and studied in the newly independent Poland in the 1930s, as well as in Vienna and Paris just before the outbreak of the Second World War. During the German occupation he formed a piano duo with his friend and fellow composer Witold Lutosławski, and they performed in cafés around Warsaw. After the war, Panufnik quickly established himself as a leading Polish composer, and as a conductor he played a significant role in the re-establishment of first the Kraków and then the Warsaw Philharmonic. Although he was considered Poland's leading composer for some years after the war, Panufnik was subsequently put under intolerable pressure both musically and politically. Frustrated by the continuing rejection of his compositions and the unending political demands inflicted on him by the country's post-war Communist regime, he made a daring escape to England in 1954. He briefly became Principal Conductor of the City of Birmingham Symphony Orchestra, a post he relinquished after two years to devote all his time to composition. His works were in demand by major figures such as Leopold Stokowski who conducted the first performances of Sinfonia Elegiaca, Katyń Epitaph and Universal Prayer, Yehudi Menuhin who commissioned the Violin Concerto, Seiji Ozawa in Boston and Sir Georg Solti in Chicago who both commissioned symphonies for the centenaries of their famous orchestras; also Mstislav Rostropovich with the London Symphony Orchestra, who together commissioned the Cello Concerto.